2017
DOI: 10.1002/adma.201703552
|View full text |Cite
|
Sign up to set email alerts
|

Polar‐Electrode‐Bridged Electroluminescent Displays: 2D Sensors Remotely Communicating Optically

Abstract: A novel geometry for electroluminescent devices, which does not require transparent electrodes for electrical input, is demonstrated, theoretically analyzed, and experimentally characterized. Instead of emitting light through a conventional electrode, light emission occurs through a polar liquid or solid and input electrical electrodes are coplanar, rather than stacked in a sandwich configuration. This new device concept is scalable and easily deployed for a range of modular alternating-current-powered electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…[ 39,40 ] Thus, employing a screen‐printing technique with perovskite precursor inks would lead to the formation of perovskite arrays with high throughput [ 41 ] for the construction of self‐emitting display panels. [ 40,42 ] However, the ability of such a printing method to precisely define the physical dimensions of patterns is quite limited due to the difficulties in manipulating the flow and spread of liquid inks on surfaces, [ 43,44 ] which leads to uncontrollable geometry of individual elements, thus hampering their application as high‐quality resonators for lasing emission. One approach to overcoming this limitation is to deposit the ink onto a substrate containing a predefined surface‐energy pattern that can steer and confine the ink to specific regions.…”
Section: Figurementioning
confidence: 99%
“…[ 39,40 ] Thus, employing a screen‐printing technique with perovskite precursor inks would lead to the formation of perovskite arrays with high throughput [ 41 ] for the construction of self‐emitting display panels. [ 40,42 ] However, the ability of such a printing method to precisely define the physical dimensions of patterns is quite limited due to the difficulties in manipulating the flow and spread of liquid inks on surfaces, [ 43,44 ] which leads to uncontrollable geometry of individual elements, thus hampering their application as high‐quality resonators for lasing emission. One approach to overcoming this limitation is to deposit the ink onto a substrate containing a predefined surface‐energy pattern that can steer and confine the ink to specific regions.…”
Section: Figurementioning
confidence: 99%
“…However, the transparent conducting materials, such as the widely used AgNWs electrode, usually have poor resistance to various mechanical deformations, which will result in the device performance degradation and, to a great extent, impedes the development of AC‐TFEL device in the field of flexible electronics. To tackle the hurdle of transparency for flexible electrodes, Xu et al recently demonstrated an AC‐powered polar‐electrode‐bridged electroluminescent source (AC‐PEB‐ELS), which can be easily scaled and deployed into various emitting and sensing components . As shown in Figure a, the device components mainly comprise the two coplanar electrodes (the parallel electrode A and electrode B), the dielectric layer, the light‐emitting layer and a modulating electrode layer (namely the polar electrode bridge) which could be polar liquids (such as DI water, ethanol and NaCl solution) or solids (such as graphite, aluminum and gold).…”
Section: Optimizing Strategies For Ac‐driven El Devicesmentioning
confidence: 99%
“…Light emission by the use of a human hand as a polar electrode bridge for the panel. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Optimizing Strategies For Ac‐driven El Devicesmentioning
confidence: 99%
“…ZnS:Cu is a typical electroluminescent phosphor material that emits light via excitations within intrinsic heterojunctions under an AC electric field. Its emission colors can be easily tuned by doping with different concentrations and types of active elements [ 14 , 27 ]. The emissive layer was dip-coated onto the AgNWs inner electrode.…”
Section: Resultsmentioning
confidence: 99%